Effectiveness of Hydrilla verticillata and Lemna minor as Phytoremediator LAS in Domestic Waste Detergent - Nur, Rizma Nur Fatikasari; Purnomo, Tarzan (LenteraBio : Berkala Ilmiah Biologi, 2022)
The current problem of aquatic environment is presence domestic waste with increasing use detergents. This research aimed to evaluate effectiveness of Hydrilla verticillata and Lemna minor on fitoremediator LAS detergent concentration in domestic waste and describe the effect of LAS detergent concentration the growth of Hydrilla verticillata and Lemna minor. This research conducted experimentally used a Completely Randomized Design with two factors is concentration of LAS detergent ( 0 mg/l, 5 mg/l, 10 mg/l, 15 mg/l) and plant type (Hydrilla verticillata, Lemna minor). Parameter measured is water LAS detergent concentration, BOD concentration, and wet biomass. Supporting data is pH and temperature. This research used 3 repetitions were carried out that 36 treatment units were obtained. The data obtained analyzed using a two-way ANOVA continued Duncan test with accurancy 0,05. Supporting data is pH and temperature analyzed with descriptive. Results showed was an effect various LAS detergent concentration and plant type in decreasing of LAS detergent concentration. The highest decrease in LAS detergent concentration occurred is Lemna minor and LAS detergent concentration is 15 mg/l of 97,48%. LAS detergent concentration and plant type effective the decrease in wet biomass and decrease in BOD concentration.Results showed that Hydrilla verticillata and Lemna minor effective to reduce LAS detergent concentration in domestic waste.